A Dose-Finding Trial for Hyperthermic Intraperitoneal Cisplatin in Gynecological Cancer Patients Receiving Hyperthermic Intraperitoneal Chemotherapy - Chan, Chui-ying; Li, Hui; Wu, Miao-fang; Liu, Chang-hao; Lu, Huai-wu; Lin, Zhong-qiu; Li, Jing (Frontiers in Oncology, 2021)
Background: To identify the maximum tolerated dose (MTD) of hyperthermic intraperitoneal cisplatin at 43 °C among gynecological cancer patients. Methods: In this Phase I dose-finding trial, Bayesian optimal interval (BOIN) design was used. We sought to explore the MTD with a target dose-limiting toxicity (DLT) rate of 20%, 4 prespecified doses (70 mg/m2, 75 mg/m2, 80 mg/m2 and 85 mg/m2) and 30 patients. Results: Between 2019 and 2020, 30 gynecologic cancer patients were enrolled. No patients received bevacizumab in subsequent treatment. The most common adverse events related to cisplatin were nausea and vomiting (100%), followed by tinnitus (26.7%) and kidney injury (23.3%). Of the seven patients with kidney injury, four had persistent renal impairment and finally progressed into chronic kidney injury. DLTs were noted only in the dose level 4 group (85 mg/m2) and included acute kidney injury, pulmonary embolism, anemia and neutropenia. When cisplatin was given at dose level four (85 mg/m2), the isotonic estimate of the DLT rate (22%) was closest to the target DLT rate of 20%. Therefore, 85 mg/m2 was selected as the MTD, with a 51% probability that the toxicity probability was greater than the target DLT rate. Conclusions: For gynecological cancer patients who received HIPEC for peritoneal metastases, the MTD of cisplatin in HIPEC at 43 °C was 85 mg/m2. Our findings apply to patients who do not receive bevacizumab (ChiCTR1900021555).